2020
DOI: 10.1080/20009666.2020.1811070
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and outcomes of critically ill patients with COVID-19 in a tertiary community hospital in upstate New York

Abstract: Background : There are limited reports describing critically ill COVID-19 patients in the state of New York. Methods : We conducted a retrospective analysis of 32 adult critically ill patients admitted to a community hospital in upstate New York, between 14 March and 12 April 2020. We collected demographic, laboratory, ventilator and treatment data, which were analyzed and clinical outcomes tabulated. Results : 32 patients admitted to the intensive car… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Peak CRP level of 125 mg/dL was noticed on day 4 of non-surviving intubated patients, contrary to this surviving patients had levels below 50 mg/dL on the same day followed by a declining pattern [15]. Lowest lymphocyte count of 400 cells/µL, peak CRP levels of 214.7 mg/L, peak procalcitonin 0.4 ng/mL, peak dimer 2.02 mcg/mL, peak LDH 475 U/L, peak ferritin 1442 ng/mL, and peak thrombocytopenia of 166 x10 9 /µL were observed according to one study [16]. Another similar study compared these markers among survivors and non-survivors showed that lymphocyte count decreased significantly in both survivors (from 0.94 to 0.51 × 10 9 cells/L) and non-survivors (from 1.24 to 0.61 × 10 9 cells/L), respectively.…”
Section: Discussionmentioning
confidence: 92%
“…Peak CRP level of 125 mg/dL was noticed on day 4 of non-surviving intubated patients, contrary to this surviving patients had levels below 50 mg/dL on the same day followed by a declining pattern [15]. Lowest lymphocyte count of 400 cells/µL, peak CRP levels of 214.7 mg/L, peak procalcitonin 0.4 ng/mL, peak dimer 2.02 mcg/mL, peak LDH 475 U/L, peak ferritin 1442 ng/mL, and peak thrombocytopenia of 166 x10 9 /µL were observed according to one study [16]. Another similar study compared these markers among survivors and non-survivors showed that lymphocyte count decreased significantly in both survivors (from 0.94 to 0.51 × 10 9 cells/L) and non-survivors (from 1.24 to 0.61 × 10 9 cells/L), respectively.…”
Section: Discussionmentioning
confidence: 92%
“…As shown in Table 1 , 18 of the included studies were from Asia [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ], 10 from Europe [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ] and 12 from North American [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. 23 studies (57.5%) were conducted in single center and 17 were (42.5%) multicenter.…”
Section: Resultsmentioning
confidence: 99%
“…In only 4 (18%) studies did these demarcation thresholds exceed 16 cmH 2 O and only one reached 20 cmH 2 O. 128,144,148,150 By comparison, lower range PEEP requirements (ie. demarcated by 1 SD below the mean or 25 th percentile) were twice as frequent with 36% of studies reported values < 10 cmH 2 O.…”
Section: Peep and Tidal Volume Parametersmentioning
confidence: 97%
“…Twenty-four reviewed studies provided initial ventilator data (Table 3). 84,107,108,111,114,116,117,121,128,[141][142][143][144][145][146][147][148][149][150][151][152][153][154] In 22 of these mean/median PEEP requirements were 10-16 cmH 2 O (Table 3, Fig 1). A crude approach for determining the need for particularly high PEEP levels (ie, approaching the "super-PEEP" threshold of 20 cmH 2 O) are values demarcating 1 standard deviation (SD) above the mean, or the 75 th percentile.…”
Section: Peep and Tidal Volume Parametersmentioning
confidence: 99%
See 1 more Smart Citation